Mechanical Properties of Concrete with Bamboo Chips - Sung-Sik Park; Yao-long Hou; Jun-Cheol Lee; Sueng-Won Jeong (Applied Sciences, 2019)
Mechanical properties of concrete with bamboo chips as a potential source of aggregates have been investigated in this study.The measurement of this investigation includes slump loss, compressive strength, strain at peak compressive stress, modulus of elasticity, compressive toughness ratio, and splitting tensile strength. A 0.5-cm-thick bamboo chip was cut to a 1 cm (width) × 1 cm (height) piece and then dried, wetted, and coated to minimize water absorption.The coarse aggregates in the concrete specimen were replaced with 10%, 20%, and 30% (by volume) of each bamboo chip. The testing results showed that the compressive strength and splitting tensile strength of concrete with bamboo chips decrease with increasing bamboo chip content (BCC). It is considered that the decrease of strengths is due to the weak bond between the mortar and the bamboo chip.